Response of rural landscape disturbance changes to human activities in karst mountainous areas - Huiqing Han; Jian Zhu; Yue Liu; Yingjia Zhang (Ciência Rural)
ABSTRACT: Landscape patterns in mountainous areas with rapid economic development are strongly affected by multiple human activities. However, the changes in landscape disturbances across karst mountainous areas attributed to complex human activities remain unclear. Research on the degree of landscape disturbance in mountainous areas under the influence of human activities is of great significance to the conservation and scientific management of mountainous landscapes. We selected rural zones with four typical small-scale landform types in karst mountainous areas as the research objects and analyzed the response of changes in rural landscape disturbance to human activity in these areas. Our results revealed that the landscape disturbance degree and human activity influence index increase in the majority of karst mountainous areas. The changes in human activity and landscape disturbances are generally observed in the low terrain relief region. High-intensity land use associated with rapid economic development has a serious negative impact on the degree of landscape disturbance, while ecological restoration projects exert a positive impact. Accelerating the implementation of the grain for green project and regulating the unregulated expansion of production and living land are crucial measures for the ecological management in karst mountainous areas. Future ecological management strategies should focus on relatively flat terrain areas. Our findings contributed to the landscape management and human activity regulation of different small-scale landform types in karst mountainous areas.